New developments in mechanisms of prostate cancer progression. (August 2019) - Howard, Nicholas; Clementino, Marco; Kim, Donghern; Wang, Lei; Verma, Angela; Shi, Xianglin; Zhang, Zhuo; DiPaola, Robert S.
Abstract: Prostate cancer is the most prevalent type of cancer in men. The etiology of prostate cancer development and the mechanisms underlying androgen-independent progression remains to be further investigated. There are many known targets for prostate cancer therapy including the androgen receptor (AR) axis, but resistance eventually develops in advanced disease suggesting the need to better understand mechanisms of resistance and consideration of multi-targeted therapy. Mechanisms contributing to resistance may include gene amplifications, gene mutations, AR splice variants, and changes in expression of androgen receptor co-regulatory proteins. Given the limitations of approved therapies, further study of additional potential targets is warranted. This review focuses on the roles of autophagy pathway, p62, Yes-associated protein (YAP), cancer stem cells, and epigenetics. Therapies targeting these potential mechanisms of resistance may interact with currently approved therapies either additively or synergistically. Thus, the study of combination therapy against multiple targets may be critically important to achieve more impact against lethal forms of prostate cancer resistant to all approved current therapies.